2020
DOI: 10.7717/peerj.10267
|View full text |Cite
|
Sign up to set email alerts
|

Improving decolorization of dyes by laccase from Bacillus licheniformis by random and site-directed mutagenesis

Abstract: Background Dye wastewater increases cancer risk in humans. For the treatment of dyestuffs, biodegradation has the advantages of economy, high efficiency, and environmental protection compared with traditional physical and chemical methods. Laccase is the best candidate for dye degradation because of its multiple substrates and pollution-free products. Methods Here, we modified the laccase gene of Bacillus licheniformis by error-prone PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…It is somewhat different from other bacterial laccases. To date, it has been reported that bacterial laccases predominantly come from Bacillus, Pseudomonas and Streptomyces (Christopher et al 2014;Bu et al 2020). Bacterial laccases are generally active and stable at nearnormal human body temperature and a neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…It is somewhat different from other bacterial laccases. To date, it has been reported that bacterial laccases predominantly come from Bacillus, Pseudomonas and Streptomyces (Christopher et al 2014;Bu et al 2020). Bacterial laccases are generally active and stable at nearnormal human body temperature and a neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results could provide a path to improve catalytic activity of CtLac with further investigation of molecular structure. Indeed, most investigations on mutagenesis to enhance enzyme activity have been performed between well-known laccases with high amino acid identities, such as Bacillus licheniformis and Bacillus subtilis [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our results could provide a pathway for improving the catalytic activity of CtLac by investigating the molecular structure further. Indeed, most investigations on mutagenesis to enhance enzyme activity have been performed between well-known laccases with high amino acid identities, such as Bacillus licheniformis and Bacillus subtilis (Bu et al 2020 ; Mollania et al 2011 ; Wang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%